The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.1149/1.2133490
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐Implanted Gallium‐Arsenide‐Phosphide Surfaces

Abstract: Study of thermal degradation of mechanical surface perfection and surface photoluminescence (PL) of GaAs0.6P0.4 samples, some of which received high dose room temperature Zn + or Ar + ion implants and others of which were unimplanted, strongly suggests that PL degradation and thermal etch pit formation have a common origin. Thermal etch pits are believed to nucleate at dislocations reaching the surface and these same dislocations act as sources of vacancy injection into the bulk, resulting in PL degradation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In the present case, we consider that annealing-induced PL degradation in GaP(0 0 1) results from production of competing nonradiative surface recombination centres of some sort, including P vacancies produced at the near surface. It was already reported that PL degradation and thermal etch pit formation have a common origin [34]. Thermal etch pits are believed to nucleate at dislocations reaching the surface and these same dislocations act as sources of vacancy injection into the bulk GaP, resulting in PL degradation [3].…”
Section: Pl Measurementmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present case, we consider that annealing-induced PL degradation in GaP(0 0 1) results from production of competing nonradiative surface recombination centres of some sort, including P vacancies produced at the near surface. It was already reported that PL degradation and thermal etch pit formation have a common origin [34]. Thermal etch pits are believed to nucleate at dislocations reaching the surface and these same dislocations act as sources of vacancy injection into the bulk GaP, resulting in PL degradation [3].…”
Section: Pl Measurementmentioning
confidence: 99%
“…It was already reported that PL degradation and thermal etch pit formation have a common origin [34]. Thermal etch pits are believed to nucleate at dislocations reaching the surface and these same dislocations act as sources of vacancy injection into the bulk GaP, resulting in PL degradation [3].…”
Section: Pl Measurementmentioning
confidence: 99%
See 2 more Smart Citations